PERCEPTION OF ECOTOURISM SUSTAINABILITY FACTOR AMONG A THOUSAND ISLAND MANGROVE POPULATIONS - Hamzah Muhammad Mardiputra (DPPM Universitas Pelita Bangsa, 2018)
The objective of this study is to analyze difference of variable before and after of the impact ecotourism factor with dependent samples t-test. This research uses quantitative methods through field surveys of a sample size of 40 respondents taken from a population of 23.000 population I Thousand Island District of DKI Jakarta. This sample size uses the purposive sampling of resident live in Sepa Island before ecotourism and after ecotourism with variable Economic Sustainability, Social Culture Sustainability, Environment Sustainability and Quality of Life. Conclusion of the research are There are significant differences between Economic Sustainability, Socio-cultural and Environment factor with t-test and p-value significant on clusters without (before) ecotourism and with (after) ecotourism in terms of education, employment, and monthly income of respondents. However, there were no differences in terms of Quality of Life. Keywords: Perception of Ecotourism; Sustainability, Thousand Island,